Pattern of Fatal Cranio-Cerebral Injuries in Mumbai Region - Wankhede, Mahendra Namdeo; Magare, Rupali Uttam; Nanandkar , S D (Journal of Indian Academy of Forensic Medicine, 2014)
Head injury is a leading cause of death and disability around the globe and presents a major worldwide social, economic, and health problem. With increasing civilization there is increase in road surface transport to fulfil the need of population, due to this the most common cause of head injury is vehicular accidents. Cases for present study were selected from the medico-legal autopsies, conducted at the Grant Medical College, Sir J. J. Hospital, Mumbai, during the period of 18 months, from January 2009 to August 2010. Cases (100) having a definite history of head injuries irrespective of predisposing factors, were selected for the purpose of scrutiny. From the head injury cases so scrutinized, fatal cases were isolated where the cranio-cerebral injuries alone occurred. In this study Road traffic accident is the most common cause of head injury, linear type of parietal and temporal bone fracture is mostly seen. Incidence of subarachnoid hemorrhage is most common.